How will the introduction of the sugar tax affect the consumption habits of households in Poland? - Wolak, Jacek (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Numerous scientific studies indicate a significant relationship between the number of sugar-sweetened beverages consumed and the problem of overweight and obesity. This, in turn, is a significant risk factor for many diseases, especially type 2 diabetes. Poland is a country where the consumption of sugar, especially in a processed form that is dangerous to health, is constantly growing. As a result, now two-thirds of the society are struggling with the problem of overweight, while obesity can be said in every fourth case, the forecasts are even more pessimistic. Recently, a fiscal policy with the use of the “sugar tax” is a popular tool to combat the growing consumption of sweetened beverages. The Polish government is also following this path, and the tax is scheduled to be in force at the beginning of 2021. Aim: The aim of the study is to analyse the impact of the sugar tax on prices and, consequently, on the future consumption of sweetened beverages and other related goods. Results: Based on the data of the Central Statistical Office concerning household expenditure in 2018, the complete demand model was estimated, considering demographic variables. As a result, the price and profit elasticities of demand for sweetened drinks and related goods were estimated. The results obtained in the study indicate that the introduction of the sugar tax will reduce the consumption of SSB, and the size of the changes depends on the analysed demographic factors. The decrease in consumption of sweetened beverages will increase the interest in beverages with a lower sugar content.